Influence of genetic variants on renal uric acid handling in response to frusemide: an acute intervention study. Issue 1 (11th April 2017) - Dalbeth, Nicola; Allan, Jordyn; Gamble, Gregory D; Phipps-Green, Amanda; Flynn, Tanya J; Mihov, Borislav; Horne, Anne; Doughty, Robert; Stamp, Lisa K; Merriman, Tony R
Abstract : Objectives: Genetic variation in the renal urate transporters SLC2A9 (GLUT9) and SLC22A11 (OAT4) has been reported to interact with diuretics to increase the risk of developing gout. The aim of this study was to determine whether variation in SLC2A9 or SLC22A11 influences acute renal handling of uric acid in response to frusemide. Methods: Following an overnight fast, healthy participants (n=100) attended a study visit with oral intake of 40 mg frusemide. Blood and urine samples were obtained at baseline and 30, 60, 120 and 180 min after frusemide intake. The primary end point was change in fractional excretion of uric acid (FEUA). Results: Following intake of frusemide, FEUA initially increased (mean (SD) change from baseline +1.9% (3.0%) at 60 min, p<0.001) and then decreased (mean (SD) change from baseline −1.5% (2.1%) at 180 min, p<0.001). A very small increase in serum urate was observed over the study period (mean (SD) change from baseline 0.007 (0.01) mmol/L at 180 min, p<0.001). The presence of the urate-lowering and gout-protective alleles for SLC2A9 ( rs11942223 and rs13129697 ) and SLC22A11 ( rs207826 ) did not significantly alter the FEUA following a frusemide load. At both 60 and 180 min, change in fractional excretion of sodium was independently associated with change in FEUA (standardised β≥0.40, p<0.001). Conclusions: The tested variants in SLC2A9 and SLC22A11 do not influence acute changes in renal handling of uric acid in response to frusemide. Trial registration number: ACTRN12614000871640 ; Results.